Supply Chain Performance in the Wooden Furniture Industry: The Effect of Institutional Pressures and Supply Chain Integration in a Developing Country Context - Tukamuhabwa, Benjamin R.; Mutebi, Henry; Ojok, Ballam A. (Journal of African Business, 2023)
The purpose of this paper is to investigate the relationship between institutional pressures, supply chain integration and supply chain performance in the wooden furniture industry. Cross-sectional survey data collected from 86 registered wooden furniture firms in Uganda were analyzed using Partial Least Square Structural Equation Modeling. The study revealed that institutional pressures are positively and significantly related with supply chain performance and that supply chain integration plays a partial mediating role in the institutional pressures-supply chain performance relationship. Further, our component level analysis of institutional pressures reveals that whereas coercive pressure has a discernible positive influence on both supply chain integration and supply chain performance, mimetic pressure does not, while normative pressure positively influences only supply chain integration. These results underline the need to understand the role of individual components of institutional pressures and integration requirements in strategic supply chain management practice in order to boost supply chain performance of the wooden furniture firms.
Keywords: Institutional pressures; Supply chain integration; Supply chain performance; Wooden furniture; Developing country